السرطان القولوني المستقيمي - دبرها محمود; قنجراوي أكثم; دلول زياد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 80 مريضاً لديهم سرطان قولوني مستقيمي، تمّ قبولهم في مشفى الأسد الجامعي باللاذقية من أجل التشخيص والعلاج خلال سبعة أعوام (2000-2007). معدل إصابة الإناث إلى الذكور 1,2: 1. مع قمة للحدوث بالعقد السادس من العمر 24 حالة (30%), وكانت النتائج: النسبة الأعلى لتوضع الورم كانت في السين 26 حالة (32,5%) أما في المستقيم 12حالة (15%). قسّمت حالات الدراسة إلى: منتقاة: 69 حالة (86,25%) وإسعافية: 11 حالة (13,75%). اتبعت عدة طرق جراحية في العلاج حسب كل حالة، وبعد تحضير القولونات في الحالات المنتقاة وأهم هذه الطرق: استئصال الورم مع مفاغرة (يدوية على طبقتين) بدئية دون شرج مضاد للطبيعة. السرطانة الغدية هي أكثر الأنماط التشريحية المرضية شيوعاً: 77 حالة (96,25%). (75%) من سرطانات المستقيم و(58%) من سرطانات القولون المصنفة بناءً على نظام Duke كانت في المرحلة C. نسبة وفيات بعد الجراحة (5%). The study included 80 patients with colorectal cancer who had admitted to AL-Assad Universal Hospital in Lattakia for diagnosis and treatment during 7 years between 2000-2007. Female to male ratio was 1,2: 1, with peak of incidence in the sixth decade: 24 cases (30%); and the results were: The highest percentage of localization of tumor was in sigmoid colon 26 cases (32,5%) while was in the rectum (12) cases (15%). The cases of study were divided into selective (69) cases (86,25%) and emergency: (11) cases (13,75%). Many surgical methods were applied in the treatment according to each case and after preparation of the colon. The most important strategy was tumor resection with primary anastomosis (by hand -sewn in two layers) without colostomy. Adenocarcinoma was the common pathological type (77) cases (96,25%). (75%) of rectal cancers and (58%) of colon cancers which were classified by Duke’s staging system were in C stage. Mortality after surgery was (5%).